The impact of human capital measures on firm performance: A comparison by gender, race, and ethnicity - Susan Coleman (The Journal of Entrepreneurial Finance and Business Ventures, 2005)
Prior research suggests that firms owned by women and minorities are smaller, less profitable, and less growth-oriented than those owned by white men. Prior research also suggests that firm performance is influenced by the firm owner's level of human capital in the form of education, employment experience, and life experiences that might help him to prepare for the challenges of small business ownership. This article compares the performance of firms owned by white men to those owned by white women and by minority small business owners to determine if higher levels of human capital eliminate performance gaps between them. Results reveal that firms owned by white and black women and firms owned by black men were still significantly smaller, even controlling for industry sector and various measures of human capital. Contrary to prior research, however, firms owned by women and minorities were no less profitable nor less likely to grow. The sole exception to this finding was that firms owned by Asian men were significantly less likely to exhibit sales growth than firms owned by white men.
Keywords: 650